Factors that lead to inadequate management of the system development life cycle / Khairul Azman Aziz and Mohamad Azmi Nias Ahmad - Aziz, Khairul Azman; Nias Ahmad, Mohamad Azmi (2003)
In order to avoid poor planning and unrealistic expectations, which lead to project failure, the project manager should have necessary skills to cater for the requirements, which involve in different type of projects. Apart from management skills that would help the project manager to manage the project, good project manager should be alert with project failure warning sign at anytime. They also should response immediately and always look for realistic disaster avoidance steps.